Integrating ICT into the language classroom: a case study on academics of Akademi Pengajian Bahasa UiTM / Zulkarnin Zakaria - Zakaria, Zulkarnin (2005)
The advent of Information and Communication Technology (ICT) presents both opportunities and threats to the world of education. Globalisation and the new K-economy are pressuring learning institutions to change and adapt themselves to the demands of the new educational wave. While teaching and learning is supposed to improve, the actual use of ICT among academics is found wanting. Academic staff, a very important and integral part of the whole process of ICT implementation in institutes of higher learning, are always left out in the ICT planning process. This study investigates the integration of ICT into the language classroom by the 28 academics of Akademi Pengajian Bahasa UiTM. The research used the structural equation model that examines four main factors that influence the use of ICT in classroom teaching by the academics. The results show that ICT device ownership, perceived usefulness, ICT knowledge and skills as well as perceived difficulty are the factors that determine the success of ICT integration process by the academics. While the study found that ICT is being used by some of the academics, the level of usage is still very low. Their experience and knowledge of ICT do help in their effort to integrate online technologies in the language teaching and learning activities but they were bogged down by other barriers. The perceived difficulty/barriers factor has to be addressed carefully by ICT administrators if the university were to assist academics in integrating ICT into the classroom. The academics’ recommendations discussed in this study stress on the need to include proper training and support system that allocate a large amount of time for them to prepare and research new approaches in teaching and learning using ICT.